Creative Hubs in Question Place, Space and Work in the Creative Economy - Gill, Rosalind; Pratt, Andy C.; Virani, Tarek E. (Dynamics of Virtual Work,, 2019)
Creative hubs have become a cornerstone of economic and cultural policy with only the barest amount of discussion or scrutiny. This volume offers the first interrogation of creative hubs, with ground-breaking critical writing from a combination of established scholars and new voices. Looking across multiple sites trans-nationally, and combining theoretical and empirical reflections, it asks: what are creative hubs, why do they matter, and are they making the world a better place? Creative Hubs in Question discusses creative hubs in relation to debates about creative cities, co-working spaces and workers' co-operatives. Featuring case studies from Argentina to the Netherlands, and Nigeria to the UK, the contributions address how hubs are situated in relation to projects of equality and social justice, and whether and in what ways they change the experiences of the creatives who work in them. Drawing on a range of disciplinary perspectives including sociology, geography, economics, media and communications, culture and creative industries, critical policy studies, gender studies, race and ethnicity, and urban studies, this collection will be of interest to policy makers, academics, scholars, students and practitioners across these fields. .